2016
DOI: 10.3390/genes7090061
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activation in Hematological Malignancies

Abstract: Telomerase expression and telomere maintenance are critical for cell proliferation and survival, and they play important roles in development and cancer, including hematological malignancies. Transcriptional regulation of the rate-limiting subunit of human telomerase reverse transcriptase gen (hTERT) is a complex process, and unveiling the mechanisms behind its reactivation is an important step for the development of diagnostic and therapeutic applications. Here, we review the main mechanisms of telomerase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 111 publications
1
17
0
Order By: Relevance
“…Hence in this study, we used hTERT detection to assess the telomerase activity by TRAP assay in both B-CLL patients and control individuals, and it showed that the hTERT expression detected in 34 (79.1%) patients and it was significantly higher than the control group which did not show any hTERT expression and this result is higher than Tchirkov A (Tchirkov, 2004) result which showed 59% of B-CLL patients expressed hTERT and this disparity may be related to difference between the methods that used for hTERT detection. Also, the hTERT expression in our research is correlated with other researchers that identified hTERT expression in patients malignancy in compared to normal individuals (Ropio, 2016;Bruedigam, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Hence in this study, we used hTERT detection to assess the telomerase activity by TRAP assay in both B-CLL patients and control individuals, and it showed that the hTERT expression detected in 34 (79.1%) patients and it was significantly higher than the control group which did not show any hTERT expression and this result is higher than Tchirkov A (Tchirkov, 2004) result which showed 59% of B-CLL patients expressed hTERT and this disparity may be related to difference between the methods that used for hTERT detection. Also, the hTERT expression in our research is correlated with other researchers that identified hTERT expression in patients malignancy in compared to normal individuals (Ropio, 2016;Bruedigam, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Telomerase activity and hTERT appears as a key event in the development and progression of the many diseases, whereas in acute myeloid leukemia (AML), in chronic myeloid leukemia (CML) and in B-cell diseases, it was demonstrated that telomerase activity is not required for the initiation of disease, but it is required for its maintenance (Ropio, Merlio, Soares, & Chevret, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Every cell division is accompanied by shortening of telomere sequences resulting in an "end replication problem" which triggers the activation of DNA damage pathways leading to senescence and subsequent cell death. Telomere erosion and replicative senescence limit cellular proliferation, which is considered an essential tumor-suppressive mechanism [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Telomerase expression actively maintains telomere length and hence is crucial for cellular proliferation and survival. Overexpression of telomerase plays an important role in the development of cancer, including hematological malignancies [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation